Effect of Intranasal Mupirocin Prophylaxis on Methicillin-Resistant Staphylococcus aureus Transmission and Invasive Staphylococcal Infections in a Neonatal Intensive Care Unit. (2nd April 2018) - Ristagno, Elizabeth H.; Bryant, Kristina A.; Boland, Lynette F.; Stout, Gordon G.; Junkins, Alan D.; Woods, Charles R.; Myers, John A.; Espinosa, Claudia M.
Abstract : The use of monthly intranasal mupirocin was associated with a significant reduction in the rate of methicillin-resistant Staphylococcus aureus transmission and Staphylococcus aureus invasive infection in a large neonatal intensive care unit. Resistance to mupirocin emerged over time, but it was rare and was not associated with adverse clinical outcomes. Infect Control Hosp Epidemiol 2018;39:741–745